Optimization of Rice Yield of Nutri Zinc and Inpari 32 Varieties through Fertilizer Combination in Rainfed Rice Fields of Lahat, South Sumatra, Indonesia - Ani, Fitri; Rahim, Supli Effendi; Helida, Asvic (Indonesian Soil Science Society of South Sumatra in Collaboration With Soil Science Department, Sriwijaya University, 2025)
Rice (Oryza sativa L.) is one of the main food commodities in Indonesia and has a strategic role in national food security. High quality rice production is a major factor in meeting the increasing consumption needs of the community. However, agricultural conditions in Indonesia still face various challenges, especially in rainfed rice fields which are highly dependent on rainfall and often experience problems in crop production. This research was conducted in Prabu Menang Village, East Merapi District, Lahat Regency, South Sumatra Province, from January to April 2024. The method used was quantitative research with a split plot design. The main plot was a combination of fertilizers consisting of three treatments: (1) NPK (300 kg/ha), Urea (150 kg/ha), and LOF (Liquid Organic Fertilizer) (25 ml/L) ; (2) NPK (300 kg/ha) and Urea (150 kg/ha) fertilizer; and (3) LOF (25 ml/L). The subplots consisted of two rice varieties, Nutri Zinc and Inpari 32, so there were 6 treatment combinations repeated 4 times, resulting in a total of 24 units experimental . This study aimed to analyze the effect of fertilizer combinations on the growth and yield of Nutri Zinc and Inpari 32 varieties in rainfed fields. The results showed that the combination of fertilizers had significant effect on plant height and number of tillers. Inpari 32 variety was with superior higher plant height and more tillers than the Nutri Zinc variety. The combination of NPK, Urea, and LOF fertilizers with the Inpari 32 variety produced the highest productivity of 4.67 tons/ha, while Nutri zink variety with the same fertilizer is 4.41 tons/ha. The combination of NPK and Urea fertilizers with the Inpari 32 variety is 4.60 tons/ha and Nutri zink variety is 4.35 tons/ha. The use of LOF alone resulted in a lower number of tillers and productivity, 3.92 tons/ha for Inpari 32 variety and 3.66 tons/ha for Nutri Zink variet.